Pengaruh Pelaksanaan Program Usaha Kesehatan Sekolah (UKS) terhadap Perilaku Hidup Bersih Dan Sehat (PHBS) pada Remaja di Sekolah Menengah Pertama Negeri 1 Merauke Papua Selatan: The Effect of Implementing the School Health Program (UKS) on Clean and Healthy Living Behavior (PHBS) in Adolescents at SMP Negeri 1 Merauke, Papua Selatan - Umakaapa, Muktamar; Suradji, Febry Ramadhani (Jurnal Diskursus Ilmiah Kesehatan, 2024)
Background: Health promotion activities in schools are a strategic step in improving student health, one of which can be done through the implementation of the School Health Program (UKS). Aims: This study aims to determine the relationship between the UKS program and Clean and Healthy Living Behavior (PHBS) in adolescents at SMP Negeri 1 Merauke. Methods: The population of this study was all students of class X SMP Negeri 1 Merauke, totaling 105 people. The sampling technique used random sampling. The research sample was 56 respondents. This type of research is quantitative analytic research using a cross-sectional design. Data analysis was carried out univariately and bivariately using the Chi-Square test. Results: The results showed that there was no relationship between health education and students' Clean and Healthy Living Behavior (PHBS) (p-value = 0.854). Similarly, there was no relationship between health services and PHBS students (p-value = 0.584), and there was a relationship between School Environment Development and PHBS students (p-value = 0.024). Conclusion: It can be concluded that there is a relationship between the implementation of UKS in the aspect of school environment development and PHBS students. Thus, it is recommended that SMP Negeri 1 Merauke school pay attention to other factors that may influence students' Clean and Healthy Living Behavior.